The role of Endobronchial ultrasound guided transbronchial needle aspiration (EBUS-TBNA) for qualitative diagnosis of mediastinal and hilar lymphadenopathy: a prospective analysis - Ye, Ting (BioMed Central, 2011)
BACKGROUND: Recently EBUS-TBNA, which has a sensitivity of 94.6%, specificity of 100% and diagnostic accuracy rate of 96.3% as previously reported, has been widely used for patients with mediastinal and hilar lymphadenopathy or suspected lung cancer to get accurate diagnosis. The purpose of the current study was to evaluate the usefulness of EBUS-TBNA in obtaining cytological and histological diagnosis of mediastinal and hilar lymph nodes compared to the results obtained with conventional mediastinoscopy as previously reported, and to assess the relationship of diagnostic accuracy and number of passes and size of lymph nodes. METHODS: 101 patients with mediastinal and hilar lymphadenopathy or suspected lung cancer in our institution were included in this prospective study. EBUS-TBNA was performed in all cases. The final diagnosis was confirmed by cytology, surgical results, and/or clinical follow-up for at least 6 months. Sensitivity, specificity, accuracy, and positive and negative predictive values were calculated using standard formulas. RESULTS: In 101 patients, EBUS-TBNA was successfully performed to obtain samples from 225 lymph nodes, 7 lung masses, 1 mediastinal mass and 2 esophageal masses. 63 malignant tumors and 38 benign diseases were confirmed. Epidermal growth factor receptor mutation was detected in 10 biopsy samples, and epidermal growth factor receptor mutation was detected in 4 cases. With respect to the correct diagnosis of mediastinal and hilar lymphadenopathy, EBUS-TBNA had a sensitivity of 95.08%, specificity of 100%, positive predictive value of 100%, negative predictive value of 93.02%, and overall accuracy of 97.02%. The relationship of diagnostic accuracy and number of lymph node passes or size of lymph nodes was both insignificant (p = 0.27; p = 0.23). The procedure was uneventful without complications. CONCLUSIONS: EBUS-TBNA is an accurate and safe tool in diagnosis of mediastinal and hilar lymphadenopathy. It cannot completely replace mediastinoscopy, it may indeed reduce the number of mediastinoscopy procedures. In some cases, it can necessarily be the first-line procedure before mediastinoscopy.